The natural navigator : The Art of Reading Nature’s Own Signposts / Tristan Gooley - Gooley, Tristan
Starting with a simple question - 'Which way am I looking?' - Tristan Gooley blends natural science, myth, folklore and the history of travel to introduce you to the rare and ancient art of finding your way using nature's own sign-posts, from the feel of a rock to the look of the moon.